Correction: Skilled birth care uptake among women from socially disadvantaged minorities in the Kambata-Tambaro Zone, Southern Ethiopia. - Abebe Alemu; Biruk Assefa; Ritbano Ahmed; Hassen Mosa; Negesso Gebeyehu (PLOS Global Public Health)
[This corrects the article DOI: 10.1371/journal.pgph.0001238.].